Semen Semenovich Zimnitsky’s contribution to the description of the clinic of infectious diseases, microbiology and immunology - V. N. Oslopov; E. V. Khazova; S. V. Khaliullina; N. R. Khasanov; Yu. V. Oslopova; Yu. S. Mishanina; D. V. Oslopova (Кардиоваскулярная терапия и профилактика, 2023)
The early period of S. S. Zimnitsky scientific activity is characterized by a passion for microbiology, immunology and infectious diseases. Of great importance was the three-year work abroad with I. I. Mechnikov and R. Virkhov. S. S. Zimnitsky gained worldwide fame for his discovery of Manchurian typhus. S. S. Zimnitsky investigated blood complements, proved the presence of "group immuniziny", treated croupous pneumonia with monovalent serum. An analysis of S. S. Zimnitsky works in the field of infectious diseases, microbiology and immunology, several biochemical studies indicate the great contribution of the scientist to the development of Russian biological science.